Formation, Evolution and Development of Public Service Delivery in Developed Countries (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the historical development and modernization of the civil service system in developed countries. In the middle of the 20th century, the process of transition from the bureaucratic management model to the principles of New Public Management (NPM) was highlighted. This approach is aimed at increasing efficiency, privatization, and the development of contractual relations. The study discusses the principles of public service developed by L. Rollan - continuity, flexibility, equality, neutrality, and transparency. Issues of ensuring public control and transparency through information centers established in countries such as Canada and Poland will also be discussed. The article highlights public-private partnership (PPP) and its role in improving public services. It also analyzes how e-government and digital technologies are used in the experience of Europe and the USA.